Quantitative Analysis of the Topological Structure of Rock Pore Network. (14th June 2021) - Ye, Dayu; Liu, Guannan; Luo, Ning; Gao, Feng; Zhu, Xinmin; Yue, Fengtian
Abstract : As the most significant nonlinear reservoir, the rocks have complex structural characteristic. The pore structure of the rock is varied in shape and complex in connectivity. However, the prevailing methods for characterising the microstructure of rocks, such as the coordination number method and fractal theory, are still difficult to quantify the structural properties. In this study, based on the CT-scan method and a new complex network theory, the topological characteristics of rocks such as seepage path selection, degree of pore aggregation, pore importance, and pore module structure are analysed. The results show that the scale-free network model is more reliable in characterising the rock pore network than previously published structural models, and a small number of pores are the "key" to the seepage process. Besides, we proposed a new method to quantify the importance of rock pores and present the distribution characteristics and connectivity laws of the rock-pore network. This provides a new method to study the seepage process of the nonlinear reservoirs.